Особливості опушення рослин Calluna vulgaris (L.) Hull та його сортів - Kuznetsova, M.S.; Vakulenko, T.B. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2017)
Objective – to study the trichomes of the stem and leaves of the common heather (C. vulgaris (L.) Hull) and its cultivars belonging to different cultivars groups. Material and methods. Annual shoots of heather and its cultivars were examined under light microscopes Stemi-2000-C and MBS-3, increasing by 40, 50 and 100 times. Results. There are two types of trichomes on the leaves of the heather of ordinary and investigated cultivars – simple and glandular. Simple trichomes are most often located on the stem and along the edge of the leaf blade and groove, which opens the stomata. Conclusions. Length, density of location on the surface of the leaf and stem and the direction of growth of trichomes in heather and its cultivars differ. Simple trichomes on the stem are located more densely than on the leaf. The longest trichomes of the leaf and stem are on plants of the cultivar 'H.E. Beale', the shortest – on plants of the cultivar 'Golden Carpet'. Simple trichomes are located the most densely on the cultivar 'Silver Knight'. The trichomes of the leaf are directed acroscopically on the heather and its cultivars, the trichomes of the stem are chaotic on 6 cultivars. They are directed basically on the common heather and on cultivar 'Mullion', acroscopically — on two cultivars and almost horizontally — on the 'Golden Carpet'.